Developing a GIS Model for Identifying Bear Corridors with Open-Source Data: The Romanian Context - Sanda Roșca; Alexandru Chira; Iuliu Vescan; Ștefan Bilașco; Ioan Fodorean; András-István Barta; Vasile Ceuca; Paul Sestraș (Applied Sciences)
The brown bear (Ursus arctos arctos) is the only bear species on the Romanian territory, its natural habitat occupying a third of the country’s surface, including the entire mountain area as well as the hills in the immediate vicinity. The bear population in Romania is the largest in Europe, increasing every year due to legislative protection, the species being present in Annex II of the Habitats Directive. The fragmentation of the bears’ habitat is the main cause of conflict occurrences between bears and the human population, which have occurred increasingly often in recent years. The main aim of this study is the ecological diagnosis of lands populated with bears in Romania to identify the highest quality habitats within the hunting grounds and to identify possible ecological corridors aimed at preserving the connectivity between them, using GIS spatial analysis techniques and taking into account the ecological conditions needed for the brown bear to survive. Following the spatial modelling of the open-source data, it was possible to observe the presence of habitats of the highest quality that could support a bear population outside the areas where bear specimens are concentrated (the counties of Mureș, Bistrița, Harghita, Covasna, Neamț, Buzau, Vrancea, Prahova, Brașov, Sibiu, and Argeș). The analysis of these habitats, where the bear population has exceeded the optimal level that they can support, highlighted that to allow the passage of bear specimens from one habitat to another, it is necessary to create ecological corridors in several key areas deducted on the basis of mathematical models.